GRIN2B encephalopathy: novel findings on phenotype, variant clustering, functional consequences and treatment aspects. Issue 7 (4th April 2017) - Platzer, Konrad; Yuan, Hongjie; Schütz, Hannah; Winschel, Alexander; Chen, Wenjuan; Hu, Chun; Kusumoto, Hirofumi; Heyne, Henrike O; Helbig, Katherine L; Tang, Sha; Willing, Marcia C; Tinkle, Brad T; et al.
Abstract : Background: We aimed for a comprehensive delineation of genetic, functional and phenotypic aspects of GRIN2B encephalopathy and explored potential prospects of personalised medicine. Methods: Data of 48 individuals with de novo GRIN2B variants were collected from several diagnostic and research cohorts, as well as from 43 patients from the literature. Functional consequences and response to memantine treatment were investigated in vitro and eventually translated into patient care. Results: Overall, de novo variants in 86 patients were classified as pathogenic/likely pathogenic. Patients presented with neurodevelopmental disorders and a spectrum of hypotonia, movement disorder, cortical visual impairment, cerebral volume loss and epilepsy. Six patients presented with a consistent malformation of cortical development (MCD) intermediate between tubulinopathies and polymicrogyria. Missense variants cluster in transmembrane segments and ligand-binding sites. Functional consequences of variants were diverse, revealing various potential gain-of-function and loss-of-function mechanisms and a retained sensitivity to the use-dependent blocker memantine. However, an objectifiable beneficial treatment response in the respective patients still remains to be demonstrated. Conclusions: In addition to previously known features of intellectual disability, epilepsy and autism, we found evidence that GRIN2B encephalopathy is also frequently associated with movement disorder, cortical visual impairment and MCD revealing novel phenotypic consequences of channelopathies.